2017
DOI: 10.1371/journal.ppat.1006247
|View full text |Cite
|
Sign up to set email alerts
|

Release of HIV-1 sequestered in the vesicles of oral and genital mucosal epithelial cells by epithelial-lymphocyte interaction

Abstract: Oropharyngeal mucosal epithelia of fetuses/neonates/infants and the genital epithelia of adults play a critical role in HIV-1 mother-to-child transmission and sexual transmission of virus, respectively. To study the mechanisms of HIV-1 transmission through mucosal epithelium, we established polarized tonsil, cervical and foreskin epithelial cells. Analysis of HIV-1 transmission through epithelial cells showed that approximately 0.05% of initially inoculated virions transmigrated via epithelium. More than 90% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(68 citation statements)
references
References 130 publications
4
60
0
Order By: Relevance
“…Our findings show that HIV endocytosis and macropinocytosis lead to sequestration of virions into late endosomes, including MVB and vacuoles. As we showed recently (Yasen et al, 2017), the interaction of activated lymphocytes with epithelia sequestering HIV-1 initiates the spread of virus from epithelial cells into lymphocytes. Thus, intravesicular HIV-1 sequestration may contribute to the molecular pathogenesis of viral spread from mucosal epithelial cells to virus-susceptible immune cells.…”
Section: Introductionmentioning
confidence: 60%
See 4 more Smart Citations
“…Our findings show that HIV endocytosis and macropinocytosis lead to sequestration of virions into late endosomes, including MVB and vacuoles. As we showed recently (Yasen et al, 2017), the interaction of activated lymphocytes with epithelia sequestering HIV-1 initiates the spread of virus from epithelial cells into lymphocytes. Thus, intravesicular HIV-1 sequestration may contribute to the molecular pathogenesis of viral spread from mucosal epithelial cells to virus-susceptible immune cells.…”
Section: Introductionmentioning
confidence: 60%
“…We have shown that HIV-1 sequestration is gradually reduced at later time points (Yasen et al, 2017). This suggests the possible fusion of vesicles containing HIV-1, including MVB and vacuoles, with highly acidic lysosomes, which may inactivate the virus.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations